Improving Community Financial Literacy through Financial Education Seminar and Assistance in Making Business Identification Numbers (NIB) in Mundu Mesigit Village - Widya Widya; Hanifah Hanifah; Devi Yulia; Mohammad Ridwan (International Journal Labs, 2025)
This community service program aims to increase financial literacy and encourage business legality through assistance in making Business Identification Numbers (NIB) for MSME actors in Mundu Mesigit Village. The low public understanding of financial management, the risk of online loans, and the lack of business legality are the basis for the need for integrated intervention. The activity was carried out through financial education seminars and technical assistance for NIB registration using the Online Single Submission (OSS) system. The method used is qualitative descriptive through observation, direct assistance, informal interviews, and published NIB documentation. The results of the activity showed that the seminar succeeded in improving participants' understanding of financial segregation, cash flow recording, and financial risk management. In addition, OSS assistance has proven to be effective, as evidenced by the issuance of 32 NIBs from 33 participants. This program not only overcomes financial and digital literacy barriers, but also strengthens the capacity of MSME actors to manage their businesses formally and sustainably. These findings confirm that the integrated intervention model is very relevant and can be replicated for the empowerment of MSMEs in other rural areas.